Determinación de la incidencia de dirofilariosis Canina por el método de frotis directo en la parroquia Pimocha del cantón Babahoyo en la provincia de Los Ríos - Moreira Moreira, Irina Lucciola (2013)
The present investigation work tried about the Incidence of Dirofilariosis canine illness it causes in dogs for the nematode Dirofilaria inmitis identify for the method of direct smear, in animal it shows in the Parish Pimocha of the canton Babahoyo in The Ríos' County. Thesize of thesamplewas of 320 animals, distributed in the sector Alegría, Centro, Crespín Cerezo, Fortuna, La Carmela, La Legua, Margarita, La Tranca, Las Malvinas, Las Palmas, Naranjillo, Naranjo, Naranjo 1, Naranjo 2, Nueva Esperanza, Porvenir, Puerto Zinc. The incidence of the illness was evaluated in function of the race, age, sex and place. The positive cases were evaluated by the Non Parametric test and Squared Chi, with the data the obtained data and the applied statistical analysis the following results were obtained: Of the 320 dogsit shows7 were positive, what represented 2, 19 % of incidence, with a sensibility of the test of diagnostic of 2, 19 %.